PENGEMBANGAN STRATEGI PEMASARAN YANG TEPAT UNTUK INDUSTRI ASURANSI HIDUP DI WILAYAH YANG DIKEMBANGKAN STUDI KASUS: ASURANSI BNI LIFE DI KOTA BANGKINANG - Samsurijal Hasan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
From time to time in human history, the world and human being were changes rapidly against the development of society. Since 1760, the are 4 times revolution in industry sector along with the human perspective and people way of life. Nowadays, life insurance is becoming one of the basic human requisites. Most of the conventional bank also expand their branch into this industry. This study is focusing to determine the precise marketing strategy for an Insurance company in order to increase the customer target. This study using two main data resource which is interview along with the questioner and research file observation including reference analysis and annual report analysis. This study was found, the strength of BNI Life insurance Bangkinang is in quadrant II with the Strengths Threats (ST) strategy meaning BNI Life insurance products can avoid threats by using the strengths owned by the company, then BNI Life insurance with these strengths must be able to seize opportunities so that the desired goals of the company can be achieved. Where, Internal factors consisting of strength with an average Total Weight Values (TWV) of 0.27 and a weakness variable with an average TVW of 0.15 with a difference of 0.12. External factors consisting of opportunity variables with an average TVW 0.22 and a threat variable with an average TVW 0.23 with a negative difference of 0.01.